Idiopathic Aneurysm of the Aortic Arch in an Infant - Cvitkovic, Tomislav; Petena, Elena; Sarikouch, Samir; Neubert, Lavinia; Beerbaum, Philipp; Horke, Alexander; Bobylev, Dmitry (The Thoracic and Cardiovascular Surgeon Reports, 2022)
Congenital aortic aneurysms are rare disorders, usually associated with genetic aortic syndromes. Here, we describe the case of an idiopathic aortic arch aneurysm which had been diagnosed prenatally by fetal echocardiography. The diagnosis was confirmed after birth in the neonatal period and successful surgical resection of the aneurysm was performed at the age of 3 months. The idiopathic etiology of the aneurysm, its localization, and the early surgical resection render this case very unusual.
Keywords: aortic arch; aneurysm; infant; cardiovascular imaging